2020
DOI: 10.3389/fenrg.2020.00066
|View full text |Cite
|
Sign up to set email alerts
|

Solar Biomass Gasification Combined With Iron Oxide Reduction for Syngas Production and Green Iron Metallurgy

Abstract: The solar gasification of biomass with iron oxide for combined syngas and iron production was investigated. Both solar energy and biomass are promising renewable energies. The process of gasification converts solid carbonaceous feedstocks into either fuels or chemicals. However, conventional processes require partial combustion of the feedstock for energy supply and inherently suffer from high oxygen production costs and low syngas calorific value due to dilution with combustion products. Chemical looping gasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…7, which is consistent with thermodynamic predictions (Fig. 5) and previous studies [36,42]. C2Hm yields between H2O and CO2 gasifying agents were found to be not significantly different.…”
Section: Influence Of H2o and Co2 Gasifying Agentssupporting
confidence: 92%
“…7, which is consistent with thermodynamic predictions (Fig. 5) and previous studies [36,42]. C2Hm yields between H2O and CO2 gasifying agents were found to be not significantly different.…”
Section: Influence Of H2o and Co2 Gasifying Agentssupporting
confidence: 92%
“…The temperature for reaction completion was slightly higher than for H 2 O gasification (above 1000 • C (CO 2 ) vs. above 900 • C (H 2 O)). This is because of the Boudouard equilibrium (Equation ( 8)) that requires a higher temperature for reaction completion [23], which translates into much slower kinetics compared to carbon gasification with H 2 O (Equation ( 9)) [28]. Figure 5 shows thermodynamic equilibrium composition of biomass gasification with solid ZnO oxidant (Equation ( 4)) as a function of temperature at 1 bar.…”
Section: Thermodynamic Equilibrium Analysismentioning
confidence: 99%
“…Solar-driven gasification with gaseous or solid oxidants was previously investigated numerically [20], experimentally [21], and economically [22]. Concerning solid oxidants, Bellouard et al [23] employed iron oxide to gasify beech wood biomass and found that iron oxide was reduced to metallic iron, depending on the oxygen carrier proportion. They also concluded that iron oxide is an effective candidate for producing both syngas and iron via a novel green metallurgical process.…”
Section: Introductionmentioning
confidence: 99%
“…Bellouard et al, 44 evaluated the relevance of biomass gasification on iron oxide in an H 2 O or CO 2 atmosphere. The composition of the produced syngas was evaluated, showing greater production of H 2 after steam oxidization.…”
Section: Production Of Co and H2 By Water‐splitting Thermochemical Cy...mentioning
confidence: 99%